Kegunaan Filsafat dalam Segala Disiplin Ilmu - Priyambodo, Mas Agus; Sayehu (At-Tadris: Journal of Islamic Education, 2024)
Philosophy is a discipline that seeks to answer fundamental questions about existence, knowledge, morals, and reality. As a critical thinking, philosophy has an important role in the development of various disciplines. By providing a framework for analyzing complex concepts, philosophy helps us understand the theoretical and practical underpinnings of science. In an academic context, philosophy serves not only as a tool for reflection, but also as a methodological guide. Through epistemology, philosophy explains how knowledge is acquired, tested and validated. In addition, philosophy also provides an ethical perspective that is indispensable in the development of science, especially when dealing with contemporary issues such as technology, the environment, and social justice. This study aims to examine the various uses of philosophy in scientific disciplines, ranging from natural sciences, social sciences, humanities, to technology. First, philosophy serves as a foundation for science. It encourages scientists to question the assumptions underlying their theories and helps them formulate deeper research questions. As such, philosophy not only enriches our understanding of the world but also directs the direction of scientific research. Second, philosophy has wide-ranging uses in a variety of disciplines, including the sciences, social sciences, education, and law. In each of these contexts, philosophy offers a perspective that allows us to explore the values, ethics, and implications of the knowledge we develop. For example, in education, philosophy helps define more inclusive learning goals and methods, while in law, philosophy allows us to examine justice and the ethical application of law. In conclusion, philosophy is an invaluable tool in developing knowledge and facing contemporary challenges. With collaboration between philosophy and other disciplines, we can create more just, humane, and sustainable solutions to the problems faced by society today